A soft computing algorithmic technique for circuital analysis of a wireless mobile charger - Olukayode Ojo, Adedayo; Oladipupo Alegbeleye, Oluwafemi; Omowunmi Olomowewe, Rashida (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Wireless energy transfer is emerging as a promising technology for mobile devices because it enhances rapid charging without requiring conventional cables. In this paper, a wireless mobile charger circuit was designed and simulated, the data obtained thereof was used to train an artificial neural network (ANN) using Levenberg-Marquardt (LM) algorithm. The result obtained was validated against that obtained when trained with regular scaled conjugate algorithm. Analysis of the results showed that the proposed technique remains a viable technique for rapidly analyzing several parts of the wireless mobile charger circuit for design and educational purposes, without always executing computationally intensive and time-consuming simulations.